This is America's story - Wilder, Howard Baker, 1901-; Ludlum, Robert Phillips, 1909-; Brown, Harriett McCune, 1897-; Roberts, Susan A., 1943- (Boston : Houghton Mifflin, 1983)
A history of the United States through the Reagan administration. Includes study helps and reference material such as a copy of the Declaration of Independence and a complete annotated text of the Constitution.
"Teacher's edition" (71 p.) precedes t.p.
"The Constitution of the United States": p. 730-758.
Includes index.
Bibliography: p. 58-71.
900-999
Keywords: United States -- History -- Juvenile literature; United States -- History; History